The Vital Role Of The Soil In The Preservation Of Life On Earth. A Brief Look At Mexico - LOPEZ SANTOS, ARMANDO (REVISTA TERRA LATINOAMERICANA, 2024)
In recent decades, various soil functions have been identified that are integrated into four ecosystem services: provision, regulation, support and cultural. Countries like Mexico should not be the exception in promoting and promoting this recognition. The aims of this document are the following: 1) evaluate the current situation of soil resources as a matter of global security, based on the ecosystem services it provides; 2) describe the importance of building knowledge about soil in relation to the human condition; and 3) place the relevance of soil as a central issue in knowledge management for problem solving. This document integrates information from sources specialized in the development of knowledge in the field of Soil Science and related areas, with the purpose of supporting key ideas towards the hedonic valuation of the soil. The holistic nature of soil, alone, not only defines its importance and value in the stability and preservation of terrestrial life, but also justifies the adoption of a transdisciplinary approach with the participation of, for example, biologists, geologists, anthropologists, chemists, and economists, among others.